Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 5 - Exponents and Polynomials - 5.4 - Dividing by Monomials - Problem Set 5.4: 30

Answer

$-7n^2+9$

Work Step by Step

Recall the following rule: $\frac{a^{m}}{a^{n}}=a^{m-n}$ In order to solve this problem, use the rule above and cancel out common factors that are in both the numerator and the denominator of the fraction. $=\dfrac{-42n^6}{6n^4} + \dfrac{54n^4}{6n^4} \\=-7n^{6-4} + 9n^{4-4} \\=-7n^2+9n^0 \\=-7n^2+9(1) \\=-7n^2+9$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.